The mussel caging approach in assessing biological effects of wastewater treatment plant discharges in the Gulf of Finland (Baltic Sea). Issue 1 (15th August 2015) - Turja, Raisa; Lehtonen, Kari K.; Meierjohann, Axel; Brozinski, Jenny-Maria; Vahtera, Emil; Soirinsuo, Anna; Sokolov, Alexander; Snoeijs, Pauline; Budzinski, Hélène; Devier, Marie-Hélène; Peluhet, Laurent; Pääkkönen, Jari-Pekka; et al.
Highlights: Application of mussel caging, biomarkers, passive samplers and hydrodynamic model. Significant biomarker responses in mussels close to the wastewater discharge site. Pharmaceuticals were detected in passive samplers attached to the mussel cages. Hydrodynamic model showed spatial and temporal variation of contaminant dispersal. Abstract: Biological effects of wastewater treatment plant (WWTP) effluents were investigated in Baltic mussels ( Mytilus trossulus ) caged for one month 800 m and 1100 m from the WWTP discharge site and at a reference site 4 km away. Significant antioxidant, genotoxic and lysosomal responses were observed close to the point of the WWTP discharge. Passive samplers (POCIS) attached to the cages indicated markedly higher water concentrations of various pharmaceuticals at the two most impacted sites. Modeling the dispersal of a hypothetical passive tracer compound from the WWTP discharge site revealed differing frequencies and timing of the exposure periods at different caging sites. The study demonstrated for the first time the effectiveness of the mussel caging approach in combination with passive samplers and the application of passive tracer modeling to examine the true exposure patterns at point source sites such as WWTP pipe discharges in the Baltic Sea.